Bending Analysis of Stented Coronary Artery: the Interaction Between Stent and Vessel. (August 2019) - Shen, X.; Deng, Y. Q.; Ji, S.; Zhu, H. F.; Jiang, J. B.; Gu, L. X.
ABSTRACT: Vessel flexure can be triggered naturally by surgical operation, heart pulsation and body movement. It may affect the mechanical behavior of the stent and the existence of a stent may in turn cause vessel injury. In the present study, the finite element method is employed to study the interaction between stent and vessel during vessel flexure. Two- and four-link stents made of stainless steel 316L and magnesium alloy WE43 are considered. Results indicate that longitudinal deformation of the stent can be caused by vessel flexure, and the higher levels of stress exist in the link struts. The existence of the stent could induce significant stress concentration and straightened deformation on vessel wall in the course of vessel flexure. Stents with more links or made of harder materials show greater anti-deformation capability, thus inducing a more severe stress concentration and straightened deformation on the vessel wall. The bending direction also affects the mechanical performance of the vessel-stent system. The results obtained could provide useful information for better stent designs and clinical decisions.